Challenges and Opportunities for Sustainable Financial Management at Bank Jatah Pekanbaru - Ahmad Fauzan; Muhammad Ahyaruddin (Journal of Education Technology Information Social Sciences and Health, 2024)
Based on data from the population and civil registration office, the number of family cards recorded in the city of Pekanbaru is 334,109, if in 1 family produces 1 kg of household waste per month, then the amount of household waste produced is 334,109 kg which can pollute the environment in the city of Pekanbaru. This research uses a descriptive qualitative approach and primary data sources. Data were collected through documentation, interviews, and observation. By interviewing the Director of the Ration Bank, the researcher asked about the challenges of increasing community awareness and participation in the Ration Bank program and some of the ways the Ration Bank program can create new jobs for local communities. The results of this study concluded that sustainable financial management in Bank Jatah Pekanbaru, especially in the management of used cooking oil waste can provide significant economic and environmental benefits for the community. It also increases community awareness by changing the mentality that is less concerned about the environment, and there are opportunities to create new jobs and increase community participation through attractive programs and incentives.